\(a.x+9=2\frac{1}{3}\)
\(x=2\frac{1}{3}-9\)
\(x=-\frac{20}{3}\)
\(b.\frac{-5}{2}.x=\frac{1}{10}\)
\(x=\frac{1}{10}:\frac{-5}{2}\)
\(x=-\frac{1}{25}\)
a)
<=> x=\(\frac{7}{3}-9=-\frac{20}{3}\)
b)
<=> x=\(\frac{1}{10}:\frac{-5}{2}=-\frac{2}{25}\)
\(a,x+9=2\dfrac{1}{3}\)
x +9 =\(\dfrac{7}{3}\)
x =\(\dfrac{7}{3}-9\)
x =\(\dfrac{-20}{3}\)
b,\(\dfrac{-5}{2}.x=\dfrac{1}{10}\)
\(x=\dfrac{1}{10}:\dfrac{-5}{2}\)
\(x=\dfrac{-1}{25}\)
x+9=2\(\dfrac{1}{3}\)
x+9=\(\dfrac{7}{3}\)
x =\(\dfrac{7}{3}-9\)
x =\(\dfrac{-20}{3}\)
b.\(\dfrac{-5}{2}x=\dfrac{1}{10}\)
\(x=\dfrac{1}{10}:\dfrac{-5}{2}\)
\(x=\dfrac{-1}{25}\)
a. x + 9 = \(2\dfrac{1}{3}\) b. \(\dfrac{-5}{2}\). x = \(\dfrac{1}{10}\)
\(\Rightarrow\) x + 9 = \(\dfrac{7}{3}\) \(\Rightarrow\) x = \(\dfrac{1}{10}\) : \(\dfrac{-5}{2}\)
\(\Rightarrow\) x = \(\dfrac{7}{3}-9\) \(\Rightarrow\) x = \(\dfrac{1}{10}\) . \(\dfrac{-2}{5}\)
\(\Rightarrow\) x = \(\dfrac{-20}{3}\) \(\Rightarrow\) x = \(\dfrac{-1}{25}\)